2003
DOI: 10.1042/bj20030382
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human ornithine decarboxylase activity by enantiomers of difluoromethylornithine

Abstract: Racemic difluoromethylornithine (D/L-DFMO) is an inhibitor of ODC (ornithine decarboxylase), the first enzyme in eukaryotic polyamine biosynthesis. D/L-DFMO is an effective anti-parasitic agent and inhibitor of mammalian cell growth and development. Purified human ODC-catalysed ornithine decarboxylation is highly stereospecific. However, both DFMO enantiomers suppressed ODC activity in a time- and concentration-dependent manner. ODC activity failed to recover after treatment with either L- or D-DFMO and dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 26 publications
5
55
1
Order By: Relevance
“…Later research revealed another drawback of oral eflornithine. In rat liver, L-eflornithine (L-difluoromethylornithine) was more effective in irreversibly inhibiting ornithine decarboxylase than D-eflornithine (D-difluoromethylornithine) (128). The mean bioavailability of L-and D-eflornithine in rats was 41% and 62%, respectively, indicating that eflornithine exhibits enantioselective absorption, the more potent L-isomer being less favoured (129).…”
Section: Eflornithinementioning
confidence: 96%
See 2 more Smart Citations
“…Later research revealed another drawback of oral eflornithine. In rat liver, L-eflornithine (L-difluoromethylornithine) was more effective in irreversibly inhibiting ornithine decarboxylase than D-eflornithine (D-difluoromethylornithine) (128). The mean bioavailability of L-and D-eflornithine in rats was 41% and 62%, respectively, indicating that eflornithine exhibits enantioselective absorption, the more potent L-isomer being less favoured (129).…”
Section: Eflornithinementioning
confidence: 96%
“…A variety of explanations have been put forward to explain the origin of gambiense HAT outbreaks and their tendency to recur (128). Many factors are probably involved; they include sudden modifications to the environment (e.g.…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of well studied ornithine decarboxylase, only L-Orn is a substrate, whereas the D-isomer is a competitive inhibitor (31). However, in the case of ␣-difluoromethylornithine, which is an enzyme-activated inhibitor of ornithine decarboxylase, both L-and D-isomers are substrates (32), since the inhibitor must be first decarboxylated in order to produce a reactive intermediate, which is responsible for the irreversible inhibition of the enzyme (33). We tested several aldehydes in PAO-dependent oxidation of (R)-and (S)-MeSpd (Table 1 and supplemental Table S1).…”
Section: Tablementioning
confidence: 99%
“…Eflornithine elicits its pharmacological effect by irreversible inhibition of ornithine decarboxylase, blocking polyamine biosynthesis in trypanosomes (3,18). It has also been shown that compared to D-eflornithine, the L-enantiomer exhibits Ͼ20 times higher affinity for the target enzyme ornithine decarboxylase in mammalian cells (18).…”
mentioning
confidence: 99%